2005
DOI: 10.1161/01.atv.0000151283.33976.e6
|View full text |Cite
|
Sign up to set email alerts
|

Betaine and Folate Status as Cooperative Determinants of Plasma Homocysteine in Humans

Abstract: Objective-Two published studies have demonstrated that betaine in the circulation is a determinant of plasma total homocysteine, but none had sufficient power to investigate the possible effect modification by folate status. Methods and Results-We measured homocysteine, betaine, folate, vitamin B 6 , and related compounds in serum/plasma from 500 healthy men and women aged 34 to 69 years before (fasting levels) and 6 hours after a standard methionine loading test. Choline, dimethylglycine, and folate were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
49
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 40 publications
15
49
2
1
Order By: Relevance
“…15 However, in agreement with a recent meta-analysis, 20 we did not observe any overall association between the BHMT 742 G>A genotype and extent of CAD in the present study. As in previous reports 3,14,21 plasma DMG levels in the current study were higher in men than in women. DMG was also higher among patients with established CAD risk factors, such as older age, hypertension, and smoking.…”
Section: Dmg and Other Baseline Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…15 However, in agreement with a recent meta-analysis, 20 we did not observe any overall association between the BHMT 742 G>A genotype and extent of CAD in the present study. As in previous reports 3,14,21 plasma DMG levels in the current study were higher in men than in women. DMG was also higher among patients with established CAD risk factors, such as older age, hypertension, and smoking.…”
Section: Dmg and Other Baseline Characteristicssupporting
confidence: 90%
“…8,22 B vitamins are important as cofactors in 1-carbon metabolism, and folate deficiency has been related to increased BHMT flux. 21 DMG tended to be weakly, inversely related to serum folate at baseline in nonfasting subjects, and folic acid supplementation (in WENBIT) seemed to prevent a time-dependent 4% to 10% increase in plasma DMG during follow-up. There was a positive association between baseline plasma DMG and methylmalonic acid, although no relationship was observed between DMG and cobalamin levels.…”
Section: Dmg and Other Baseline Characteristicsmentioning
confidence: 89%
“…Previous studies have shown that betaine is effective in suppressing methionine-induced hyperhomocysteinemia in humans 33,34) and rats. 35,36) In rats, Yagisawa et al 35,36) found that hyperhomocysteinemia induced by intravenous injection with methionine was suppressed by concurrent injection with betaine or dietary supplementation with betaine.…”
Section: Discussionmentioning
confidence: 98%
“…The strong effect of gender has been explained by transcriptional regulation of human BHMT by estrogen and androgen (30), and the marked relation to folate by the function of betaine and 5-methyltetrahydrofolate as interchangeable sources of 1-carbon units (8,31).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%